Assessment of the remineralisation induced by contemporary ion-releasing materials in mineral-depleted dentine - Pires, Paula Maciel; Ionescu, Andrei Cristian; Pérez-Gracia, Maria Teresa; Vezzoli, Elena; Soares, Igor Paulino Mendes [UNESP]; Brambilla, Eugenio; Neves, Aline de Almeida; Sauro, Salvatore (Springer Nature, 2022)
Objectives: Evaluate the ability of current ion-releasing materials to remineralise bacteria-driven artificial caries lesions. Materials and methods: Standardised class I cavities were obtained in 60 extracted human molars. Specimens underwent a microbiological cariogenic protocol (28 days) to generate artificial caries lesions and then were randomly divided into four restorative groups: adhesive + composite (negative control); glass ionomer cement (GIC); calcium silicate cement (MTA); and resin-modified calcium silicate cement (RMTA). Microhardness analysis (ΔKHN) was performed on 40 specimens (10/group, t = 30 days, 45 days, 60 days in artificial saliva, AS). Micro-CT scans were acquired (3/group, t = 0 days, 30 days, and 90 days in AS). Confocal microscopy was employed for interfacial ultra-morphology analysis (2/group, t = 0 days and 60 days in AS). Additional specimens were prepared and processed for scanning electron microscopy (SEM) and FTIR (n = 3/group + control) to analyse the ability of the tested materials to induce apatite formation on totally demineralised dentine discs (60 days in AS). Statistical analyses were performed with a significance level of 5%. Results: Adhesive + composite specimens showed the lowest ΔKHN values and the presence of gaps at the interface when assessed through micro-CT even after storage in AS. Conversely, all the tested ion-releasing materials presented an increase in ΔKHN after storage (p < 0.05), while MTA best reduced the demineralised artificial carious lesions gap at the interface. MTA and RMTA also showed apatite deposition on totally demineralised dentine surfaces (SEM and FTIR). Conclusions: All tested ion-releasing materials expressed mineral precipitation in demineralised dentine. Additionally, calcium silicate-based materials induced apatite precipitation and hardness recovery of artificial carious dentine lesions over time. Clinical relevance: Current ion-releasing materials can induce remineralisation of carious dentine. MTA shows enhanced ability of nucleation/precipitation of hydroxyapatite compared to RMTA and GIC, which may be more appropriate to recover severe mineral-depleted dentine.
Keywords: Dental biomaterials; Dentine replacement materials; Ion-releasing materials; Remineralisation; Restorative dentistry